Effect of Arabic gum, xanthan gum and orange oil contents on zeta-potential, conductivity, stability, size index and pH of orange beverage emulsion - Mirhosseini, H; Tana, CP; Hamid, NSA; Yusof, S (Elsevier Science Bv, 2024)
Indexed by Scopus